Каскадные переключатели резонансных СВЧ-компрессоров - Артеменко С. Н. Сергей Николаевич; Августинович В. А. Владимир Андреевич; Горев С. А. Станислав Андреевич; Новиков С. А. Сергей Автономович; Юшков Ю. Г. Юрий Георгиевич (2014, 2014)
Заглавие с экрана